PENGELOLAAN PASAR RAKYAT SEBAGAI SARANA PEMENUHAN PELAYANAN PUBLIK DI KOTA PEKANBARU - Rahman Mulya; Emilda Firdaus; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The People's Market In Pekanbaru City holds a very importantprogram for the community's economy in the city of Pekanbaru, but the poormanagement of the market has caused the market to become slum and poorlymaintained. In article 1 paragraph 16 Pekanbaru City Regulation No. 9 of2014 concerning the management of people's markets, shopping centers andsupermarkets, explains that the people's market is a business place that isorganized, built and managed by the Government, Regional Government,Private Sector, BUMN or BUMD in the form of shops, kiosks, shops.This study aims to describe how the implementation of public marketmanagement functions in the city of Pekanbaru, to find out the obstacles in themanagement of the community market, and to know what efforts must be madein managing the people's markets. This type of research is classified intosociological legal research, namely research that looks at the correlationbetween law and society, so as to be able to express the effectiveness of thevalidity of law in society and identify unwritten laws that apply to society.Conclusions can be obtained from the results of research that themanagement of the people's market in the city of administration emphasizesmore that government oversight in managing and running the existing publicmarkets in Pekanbaru, follow-up is needed regarding problems in thetraditional market such as resolving the problems that occur in traditionalmarkets.Keywords: Disperindag responsibility, market management, supervision